2018
DOI: 10.1111/resp.13330
|View full text |Cite
|
Sign up to set email alerts
|

Global Lung Initiative 2012 spirometry reference values in a large Asian cohort of Malay, Chinese and Indian ancestry

Abstract: This present and large multi-ethnic Asian-based study demonstrates clinically significant deviation from ERS/GLI 2012 equations for spirometry. It highlights the importance of validating predicted equations for spirometry in local populations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
22
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(27 citation statements)
references
References 24 publications
3
22
1
Order By: Relevance
“…Studies validating the GLI 2012 SRE have made varying conclusions, with some indicating a poor fit for local populations [10,15]. However, the FEV 1 /FVC ratio has consistently demonstrated a better fit across populations than other lung function measurements [10,[15][16][17]. Potential reasons for poor fit of SRE include sampling which is unrepresentative of the population, potential mis-specification of the prediction equations, and environmental factors such as exposure to indoor and/or ambient air pollution, malnutrition, and low socioeconomic status (SES), which may result in lower lung volumes on a population level, leading to erroneous estimations [18][19][20][21][22][23].…”
Section: Introductionmentioning
confidence: 99%
“…Studies validating the GLI 2012 SRE have made varying conclusions, with some indicating a poor fit for local populations [10,15]. However, the FEV 1 /FVC ratio has consistently demonstrated a better fit across populations than other lung function measurements [10,[15][16][17]. Potential reasons for poor fit of SRE include sampling which is unrepresentative of the population, potential mis-specification of the prediction equations, and environmental factors such as exposure to indoor and/or ambient air pollution, malnutrition, and low socioeconomic status (SES), which may result in lower lung volumes on a population level, leading to erroneous estimations [18][19][20][21][22][23].…”
Section: Introductionmentioning
confidence: 99%
“…The work of Abdullah et al ., recently published in Respirology , accepted the call from the GLI network to assess the broader global generalizability of the GLI spirometry equations . The authors obtained spirometry in over 30 000 healthy adults (aged 35–70 years) of Malay, Chinese and Indian ancestries and compared their data with that of the GLI Other equation.…”
mentioning
confidence: 60%
“…To date, many of the studies that have assessed the validity of the GLI equations have confirmed that FEV 1 /FVC is independent of ethnicity with a very close match to the GLI equations. This did not occur in the study by Abdullah et al ., in which the mean FEV 1 /FVC z‐scores ranged between 1.1 and 1.6 across the three ethnic groups assessed. These differences are not easily explained and may be influenced by unknown methodological factors or may represent true differences of the proportional distribution of flows and volumes in spirometry outcomes.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The records for 50 consecutive admissions with acute exacerbation of COPD were reviewed. The inclusion criteria included a definite history of smoking and a diagnosis of COPD based on spirometric evidence of obstruction according to European Respiratory Society criteria [8]. Exclusion criteria included a clinical diagnosis only for COPD, without any spirometric evidence, and admission to the ICU for any cause other than acute exacerbation of COPD, such as pneumonia.…”
Section: Methodsmentioning
confidence: 99%